Systematization of Methods to Counteract Counterfeiting of Premium Brands - I. P. Shirochenskaya; G. S. Timokhina; A. V. Shishkin; I. A. Koryagina; A. N. Beketov (Модернизация, инновация, развитие, 2022)
Purpose: the purpose of the article is to systematize the methods of combating counterfeiting of premium brands in order to justify the need to shift the focus from the use of methods of exclusively state regulation, mainly of a legal and technological nature, to marketing methods to curb the growth of counterfeit products for premium brands.Methods: the study is based on the use of desk methods for collecting and processing data, using methods of systemic and structural-functional assessment of actual data, methods of multidimensional classification in segmenting consumers of counterfeit products, methods of indexing and structuring marketing methods to combat counterfeit products.Results: based on the analysis of the state of the market for counterfeit premium brands and the methods used to counteract the production and distribution of counterfeit products, the authors systematized marketing methods to curb the growth of consumer demand for counterfeit products of premium brands, which made it possible to identify new methods to combat counterfeiting. As part of the systematization carried out by the authors, the types of consumers of counterfeit products of premium brands are classified based on psychographic and behavioral segmentation, as well as groups of offline, online and combined marketing methods to counter the spread of counterfeit of premium brands.Conclusions and Relevance: the results of the study will allow premium brand stakeholders to form a broader view of the set of methods used to combat counterfeit products and improve the effectiveness of the methods used.